Changes in Synapsin Levels in the Millipede Gymnostreptus olivaceus Schubart, 1944 Exposed to Different Concentrations of Deltamethrin - Francisco, Annelise [UNESP]; Nunes, Pablo H.; Nocelli, Roberta C. F.; Fontanetti, Carmem S. [UNESP] (Oxford University Press (OUP), 2016)
Millipedes are ecologically important soil organisms and may also be an economically threatening species in rural and urban areas when population outbreaks occur. In order to control infestations commercial formulations of deltamethrin have been commonly applied, even though there are few studies about the effects of such insecticide on millipedes. This paper describes the effects of this insecticide on millipedes showing neurotoxic effects assessed by synapsin labeling and confocal microscopy. Deltamethrin concentrations related to the DL50 of the active ingredient and a field concentration were applied topically in the diplopod Gymnostreptus olivaceus to evaluate the behavior, mortality rate, and synapsin levels in the brain 12, 24, and 48h after contact with deltamethin. The insecticide caused mortality at the higher concentrations employed, in which no change was observed in neurotransmission in the survivors. In contrast, at field concentrations, deltamethrin did not cause any deaths, but triggered significant changes in synapsin levels. The results obtained form the synapsin labeling provide several interpretations suggesting that the isolated application of this tool must be associated with additional tools in order to evaluate biologically induced effects of deltamethrin in an accurate way. In addition, the feasibility of chemical control of millipedes with deltamethrin is questioned.
Keywords: arthropod; confocal microscopy; diplopod; olfactory glomeruli; pyrethroid